Early Christians Adapting to the Roman Empire Mutual Recognition - Huttunen, Niko (Novum Testamentum, Supplements, 2020)
In Early Christians Adapting to the Roman Empire Niko Huttunen presents the positive relationship between early Christians and the Roman society. Non-Christian philosophers responded positively to Christians, Romans 13 belongs to the ancient political tradition, and Christian soldiers recognized the empire. Readership: All interested in the history of early Christianity, and anyone concerned with the relationship between Christianity, politics, and state.